ELECTROLESS DEPOSITION OF NI-P ALLOY ON AL-2024 USING ROTATING DISK ELECTRODE\'S MODEL - Herlambang , Karyanto
Abstract : The deposition of electroless nickel has been widely investigated due to the interesting properties of Ni-P alloys, such as corrosion and wear resistances. All of the properties of electroless nickel deposits are composition and structure dependent. This study was undertaken to gain a better understanding of deposition process each species. Electroless nickel deposition with simultaneous reactions of cathodic and anodic oxidation of reductants based on the mixed potential theory were applied The Buttle-Volmer equation was performed to calculate deposition potential and partial current density each species to predict the phosphorous content in Ni-P alloy film. The experiment shows that electroless nickel deposition using hypophosphite reductor occurs between potential range -0.574 to - 0.652 Volt. The maximum amount of phosphor is 12%. Rate of electroless nickel layering spans between 1.9 to 7.6 mAfcm2. The rate controlled using two reaction mechanisms: Metal deposition rate (catodhic reaction) is diffusion controlled while the oxidation of hypophosphite is electrochemical control. The relation between process variable and deposit rate can be simulated by a calculation program.